Antibody-mediated inhibition of syndecan-4 dimerisation reduces interleukin (IL)-1 receptor trafficking and signalling. Issue 4 (24th February 2020) - Godmann, Lars; Bollmann, Miriam; Korb-Pap, Adelheid; König, Ulrich; Sherwood, Joanna; Beckmann, Denise; Mühlenberg, Katja; Echtermeyer, Frank; Whiteford, James; De Rossi, Giulia; Pap, Thomas; Bertrand, Jessica
Abstract : Objective: Syndecan-4 (sdc4) is a cell-anchored proteoglycan that consists of a transmembrane core protein and glucosaminoglycan (GAG) side chains. Binding of soluble factors to the GAG chains of sdc4 may result in the dimerisation of sdc4 and the initiation of downstream signalling cascades. However, the question of how sdc4 dimerisation and signalling affects the response of cells to inflammatory stimuli is unknown. Methods: Sdc4 immunostaining was performed on rheumatoid arthritis (RA) tissue sections. Interleukin (IL)-1 induced extracellular signal-regulated kinases (ERK) phosphorylation and matrix metalloproteinase-3 production was investigated. Il-1 binding to sdc4 was investigated using immunoprecipitation. IL-1 receptor (IL1R1) staining on wild-type, sdc4 and IL1R1 knockout fibroblasts was performed in fluorescence-activated cell sorting analyses. A blocking sdc4 antibody was used to investigate sdc4 dimerisation, IL1R1 expression and the histological paw destruction in the human tumour necrosis factor-alpha transgenic mouse. Results: We show that in fibroblasts, the loss of sdc4 or the antibody-mediated inhibition of sdc4 dimerisation reduces the cell surface expression of the IL-1R and regulates the sensitivity of fibroblasts to IL-1. We demonstrate that IL-1 directly binds to sdc4 and in an IL-1R-independent manner leads to its dimerisation. IL-1-induced dimerisation of sdc4 regulates caveolin vesicle-mediated trafficking of the IL1R1, which in turn determines the responsiveness to IL-1. Administration of antibodies (Ab) against the dimerisation domain of sdc4, thus, strongly reduces the expression IL1R1 on arthritic fibroblasts both in vitro and an animal model of human RA. Conclusion: Collectively, our data suggest that Ab that specifically inhibit sdc4 dimerisation may support anti-IL-1 strategies in diseases such as inflammatory arthritis.